The one-step electrodeposition of nickel phosphide for enhanced supercapacitive performance using 3-mercaptopropionic acid. (30th April 2020) - Chebrolu, Venkata Thulasivarma; Balakrishnan, Balamuralitharan; Aravindha Raja, Selvaraj; Cho, Inho; Bak, Jin-Soo; Kim, Hee-Je
Abstract : TMPs have received considerable attention for various applications, including the water splitting reaction (hydrogen evolution reaction and oxygen evolution reaction), methanol oxidation, the oxygen reduction reaction, rechargeable batteries, and supercapacitors. Abstract : Transition metal phosphides (TMPs) have received considerable attention for various applications, including the water splitting reaction (hydrogen evolution reaction and oxygen evolution reaction), methanol oxidation, the oxygen reduction reaction (ORR), rechargeable batteries, and supercapacitors (SCs). Among different TMPs, nickel phosphide (NiP) is an important class, corresponding with metal chalcogenides. In the present study, NiP is fabricated from 3-mercaptopropionic acid on carbon cloth by a simple and facile electrodeposition (ED) technique. Electrochemical studies showed that carbon cloth-supported NiP exhibits better performance than NiCo2 O4 and CoP. As an active material for SCs, the electrode exhibits a specific capacitance of 227.03 F g −1 (136.22 mA h g −1 ) at a current density of 0.5 A g −1 . Further, the electrode exhibits excellent cycling stability of 81% of its initial value after 3000 cycles, which may be ascribed to the unique structural features as well as the synergistic effect of the nickel and phosphorus species with the support of carbon cloth. Hence, the low-cost ED synthesis process and carbon cloth-supported NiP show great potential for portable energy storage system applications.